Metastatic Crohn's disease - Padmavathy Lanka; Lakshmana Rao Lanka; N Sylvester; M Dhana Lakshmi; N Ethirajan (Wolters Kluwer Medknow Publications, 2014)
Crohn's disease, first described in 1922, is characterized by segmental granulomatous inflammation of the intestinal tract and frequently involves the cutaneous tissues as well. Cutaneous Crohn's disease (CCD) is synonymous with metastatic Crohn's disease (MSD). A case of CCD, without any gastrointestinal involvement is reported for its rarity.